The Paradox of Howard Becker's Intellectual Identity. Issue 12 (1st December 2016) - Goode, Erich
ABSTRACT: Howard S. Becker, best known as a sociologist of deviance, claims that he "never really did work on deviance as such." Why does he say this? The fortuitous nature of his entry into the field, his belief that deviance is not an analytic category, and the amount of time, energy, and commitment he has invested in this as opposed to other fields, play a role in this stance. In all likelihood, contrary to his wish, Howard Becker will always be regarded as a deviance researcher.